Electrochemical activity of sulfur networks synthesized through RAFT polymerization - M. R. P. F. N. Costa (2016)
Novel results concerning the inverse vulcanization of sulfur using reversible addition-fragmentation chain transfer (RAFT) polymerization are here reported. It is shown that RAFT polymerization can be used to carry out this crosslinking process, with the additional possibility to extend the reaction time from a few minutes as with classical free radical polymerization (FRP) to several hours. Higher control on viscosity and processability of the synthesized networks, as well as, the implementation of semibatch feed policies during crosslinking are important advantages of the RAFT process here explored comparatively to the FRP inverse vulcanization. Using cyclic voltammetry, it was assessed the electrochemical activity of the synthesized sulfur-rich polymer networks. It is shown that the fundamental electrochemical activity of the elemental sulfur was preserved in the produced materials. Testing of electrochemical cells assembled with lithium in the anode and different sulfur based materials in the cathode, including the synthesized RAFT networks, is also shown. The results here presented highlight the new opportunities introduced by reversible-deactivation radical polymerization mechanisms on the control of the synthesis process and in the design of such advanced materials and show also that many potential derivatizing possibilities can be achieved